2020
DOI: 10.1029/2019ja027693
|View full text |Cite
|
Sign up to set email alerts
|

Energy Flux and Characteristic Energy of Electrons Over Jupiter's Main Auroral Emission

Abstract: Jupiter's ultraviolet (UV) aurorae, the most powerful and intense in the solar system, are caused by energetic electrons precipitating from the magnetosphere into the atmosphere where they excite the molecular hydrogen. Previous studies focused on case analyses and/or greater than 30-keV energy electrons. Here for the first time we provide a comprehensive evaluation of Jovian auroral electron characteristics over the entire relevant range of energies (~100 eV to~1 MeV). The focus is on the first eight perijove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

6
2

Authors

Journals

citations
Cited by 47 publications
(90 citation statements)
references
References 106 publications
3
87
0
Order By: Relevance
“…We note that Allegrini et al (2020) map the main auroral oval as observed by Juno UVS to 50 R J using the JRM09 internal field model of Connerney et al. (2018) plus the Connerney et al.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We note that Allegrini et al (2020) map the main auroral oval as observed by Juno UVS to 50 R J using the JRM09 internal field model of Connerney et al. (2018) plus the Connerney et al.…”
Section: Discussionmentioning
confidence: 90%
“…(2019). The JADE‐E electron data were calculated using the in‐flight calibration parameters given in Allegrini et al (2020). The electron data are computed as 1‐D moments, proton data are computed from the JADE‐I Species 3 plus Species 4 products, while heavy ion data come from JADE‐I Species 5 (for more details see McComas et al., 2017).…”
Section: Datamentioning
confidence: 99%
“…In practice, the factor to normalize the distribution function is c 3 10 −18 /n e , where n e is the density (in cm −3 ). Here n e ≃ 1 cm −3 at 07:36:40, and n e ≃ 6 cm −3 at 07:37:26 and 07:37:28, and n e ≃ 2 cm −3 at 07:37:43 (see Figure 1f), which is probably slightly overestimated (Allegrini et al, 2020), leading to underestimated growth rate.…”
Section: The Cmi: Determination Of the Emission Parametersmentioning
confidence: 92%
“…This shadowing mostly affects the electrons with large pitch angles, and it also affects the lower energy more than the higher-energy electrons. The shadowing was qualitatively reproduced with a simple ray tracing simulation in Allegrini et al (2017Allegrini et al ( , 2020.…”
Section: Electron Distribution Functionmentioning
confidence: 99%
“…JEDI ion observations near the polar region have revealed both upward and downward proton beams (Mauk et al, 2017c(Mauk et al, , 2018(Mauk et al, , 2020, proton conics with much larger energies than their terrestrial counterparts (Clark et al, 2017), constrained energetic heavy ion charge states (Clark et al, 2020), and revealed an auroral environment with both similarities and significant differences to Earth's (Mauk et al, 2017c). JADE and JEDI observations have enabled the characterization of identifiable auroral zones (Allegrini et al, 2020;Mauk et al, 2020), generally organized by latitude. One of Juno's important discoveries is that Jupiter's auroral emissions can be generated (a) during mono-directional, downward acceleration-Zone I: thought to be the upward electric current region and (b) during bidirectional electron acceleration-Zone II: thought to be the downward electric current region (Mauk et al, 2020).…”
mentioning
confidence: 99%